Estimule su memoria - Rochefor Algis, Elizabeth (Barcelona Granica, 1991)
<Memorizacion><Atencion><Percepcion sensorial><Lectura><Entrevistas><Concentracion>
Keywords: COMERCIALIZACION; ADMINISTRACION DE EMPRESAS; MERCADOTECNIA